Structure and physical-mechanical properties of the electroplated composite Ag-W coatings - N. V. Bogush; A. A. Khmyl; L. K. Kushner (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Composite coatings with tungsten based on silver by electrochemical deposition were made. Influence of electrolyte composition on physical-mechanical properties and functional properties of coatings have been studied. Elements composition of deposit and an influence of the tungstate sodium concentration and deposition regimes on its structure was defined. It was established that including of tungsten oxides in the composition of silver coating allows to form a uniform coating with increased microhardness and wear resistance. Formation mechanisms of composite Ag-W coatings and using them in electronics were discussed.